Running intensity as determined by heart rate is the same in fast and slow runners in both the 10- and 21-km races - Selley, E. A.; Kolbe, T.; van Zyl, C. G.; Noakes, T. D.; Lambert, M. I. (Journal of Sports Sciences, 1995)
The aims of this study were to determine (1) whether running speed is directly proportional to heart rate (HR) during field testing and during 10- and 21-km races, and (2) whether running intensity, as estimated from HR measurements, differs in 10- and 21-km races and between slow and fast runners at those running distances. Male runners were divided into a fast (65-80 min for 21 km; n = 8) or slow (85-110 min for 21 km; n = 8) group. They then competed in 10- and 21-km races while wearing HR monitors. All subjects also ran in a field test in which HR was measured while they ran at predetermined speeds. The 10-km time was significantly less in the fast compared with the slow group (33:15 +/- 1:42 vs 40:07 +/- 3:01 min:s; mean +/- S.D.), as was 21-km time (74:19 +/- 4:30 vs 94:13 +/- 9:54 min:s) (P < 0.01). Despite the differences in running speed, the average running intensity (%HRmax) for the fast and slow groups in the 10-km race was 90 +/- 1 vs 89 +/- 3% and in the 21-km race 91 +/- 1 vs 89 +/- 2%, respectively. In addition, %HRmax was consistently lower in the field test at the comparative average running speeds sustained in the 10-km (P < 0.01) and 21-km (P < 0.001) races. Hence, factors in addition to work rate or running speed influence the HR response during competitive racing. This finding must be considered when running intensity for competitive events is prescribed on the basis of field testing performed under non-competitive conditions in fast and slow runners.